Insights Into the Role of Vitamin D as a Biomarker in Stem Cell Transplantation - Soto, Jose Ros; Anthias, Chloe; Madrigal, Alejandro; Snowden, John A. (Frontiers in Immunology, 2020)
Vitamin D was discovered 100 years ago and since then multiple studies have consistently proved its effect on bone health and mineral metabolism. Further research has also explored its so-called “non-classical” biological effects, encompassing immune regulation and control of cell proliferation and differentiation. Vitamin D downregulates pro-inflammatory immune cells and subsequently their cytokine production, while enhancing the anti-inflammatory subsets, thus mediating inflammation and fostering a more tolerogenic environment. Its biological action is exerted through the vitamin D receptor, a nuclear receptor that mediates gene transcription and is expressed in most cells from the innate and adaptive immunity. Owing to its immune-modulatory properties, its role in cancer pathophysiology, haematology disorders and stem cell transplantation has also been investigated. Vitamin D deficiency causes immune imbalance and cytokine dysregulation, contributing to some autoimmune diseases. In the haematopoietic stem cell transplant setting this could lead to complications such as acute and chronic graft-versus-host disease, ultimately impacting transplant outcomes. Other factors have also been linked to this, including specific polymorphisms of the vitamin D receptor in both stem cell donors and recipients. Nevertheless, studies thus far have shown conflicting results and the use of vitamin D or its receptor as biomarkers has not been validated yet, therefore there are no evidence-based consensus guidelines to guide clinicians in their day-to-day practice. To gain more insight in this topic, we have reviewed the existent literature and gathered the current evidence. This is an overview of the role of serum vitamin D and its receptor as biomarkers for clinical outcomes in patients undergoing haematopoietic stem cell transplantation. Further prospective studies with larger cohorts are warranted to validate the viability of using serum vitamin D, and its receptor, as biomarkers in potential stem cell donors and patients, to identify those at risk of post-transplant complications and enable early therapeutic interventions.